Simonton como leitor da Bíblia: uma análise dos seus sermões - Almeida, João Batista dos Santos (2013)
The goal of this work is to study the modes of reading of the founder missionary of the Presbyterian Church of Brazil, Ashbel Green Simonton, taking his published sermons as the main object of study. This work analyzes his life in two basic periods, in the United States of America and in Brazil, whither he came as a missionary. It proposes to analyze his sermons, by using a combination of theories of some authors, among whom are Aristotle, with his Rhetoric, Roger Chartier and his approaching to the reading materiality, and Paul Ricoeur, with his theories of metaphor and of triple mímesis, together with others thinkers. It presents a brief account of the difficulty of analyzing a sermon as a literary-discursive genre, and it concludes to be possible, at least to the purpose of this work, to analyze sermonic genre through the theoretical tools used here.